UJI IN VIVO SILASE HIJAUAN PAKAN YANG DIPUPUK AIR BELERANG DAN PUPUK KANDANG PADA DOMBA - Charles L. Kaunang; Endang Pudjiastuti (Udayana University)
This research was aimed to investigate biological value of silage forage (panicium maximum CV. Riversdale + Centrocema pubescens) without fertilization and manure 25 ton/ha + sulfuric water 50%. The experiment used 12 sheep (average liveweight 34 kg) during 28 days laters. The result showed that forage silage treatment (P. maximum CV. Riversdale + C. pubescens) with manure 25 ton/ha and sulfuric water 50% positive respons to sheep performance.